Nonsyndromic multiple supernumerary teeth: A case report of 11 supernumerary teeth - Balaji Krishnan; Balaji Narasimhan; C Nirupama (Wolters Kluwer Medknow Publications, 2012)
Hyperdontia is an odontostomatologic anomaly characterized by an excess in both erupted and non-erupted teeth number. A23-year-old female patient reported to us with a chief complaint of malaligned teeth and inability to maintain oral hygiene. Extraoral examination did not reveal any abnormality. Intraoral examination revealed multiple supernumerary teeth in maxillary and mandibular premolar region. The teeth present were: 11, 12,13,14,16,17,18.21,22,23,24,25,26,27,28,31,32,33, 34, 35. 36, 37. 38, 41. 42, 43, 44, 45. 46, 47. 48. Apart from these teeth there were. One half erupted supernumerary tooth, distal to 14, one supernumerary tooth palatal to 14, one supernumerary tooth buccal to 15, one supernumerary tooth lingual to 34, one supernumerary tooth lingual to 36, one supernumerary tooth mesio lingual to 45,1 supernumerary tooth distolingual to 45. The panoramic radiograph was taken to study the presence of impacted teeth. It revealed- Two supernumerary teeth in 1st quadrant, three supernumerary teeth in 2nd quadrant, three supernumerary teeth in 3rd quadrant, one impacted mesial to 36, three supernumerary teeth in 4th quadrant, one impacted mesial to 46. Whenever, supernumerary teeth are diagnosed , a proper decision regarding the appropriate management should be made carefully_ In our opinion, the management of multiple supernumerary teeth poses a great challenge to clinicians. Therefore, it vital to for an interdisciplinary approach for the treatment.